2023
DOI: 10.1021/acs.jpca.2c08311
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the X-ray Stark Effect in Small Molecules

Abstract: We have studied the Stark effect in the soft x-ray region for various small molecules by calculating the fielddependent x-ray absorption spectra. This effect is explained in terms of the response of molecular orbitals (core and valence), the molecular dipole moment, and the molecular geometry to the applied electric field. A number of consistent trends are observed linking the computed shifts in absorption energies and intensities with specific features of the molecular electronic structure. We find that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Here, we employ the core-valence separation (CVS) approximation, , which allows us to efficiently compute core-excited states by neglecting their interaction with excitations from the remaining occupied orbitals. CVS has been widely used for simulating core-level excited states and X-ray absorption spectra in combination with a variety of electronic structure theories. ,,,,,,,, …”
Section: Theorymentioning
confidence: 99%
“…Here, we employ the core-valence separation (CVS) approximation, , which allows us to efficiently compute core-excited states by neglecting their interaction with excitations from the remaining occupied orbitals. CVS has been widely used for simulating core-level excited states and X-ray absorption spectra in combination with a variety of electronic structure theories. ,,,,,,,, …”
Section: Theorymentioning
confidence: 99%
“…They found that aluminyl systems with carbon- and nitrogen-based chelating centers would serve well to activate hydrogen without dimerization. Finally, according to a report by Datar, Wright, and Matthews at Southern Methodist University, the presence of electric fields yields shifts in absorption energies and intensities in X-ray Stark spectra that may be attributed to responses in the molecular orbitals, the dipole moment, and the geometry . They also find that both virtual and core orbitals play a role in the observed spectral trends.…”
Section: State-of-the-art Applications Of Quantum Chemistrymentioning
confidence: 99%
“…36 The results gathered from these latter ab initio simulations fairly agree with the order of magnitude of the EFs leading to water ionization determined experimentally (i.e., ∼0.1−0.5 V/Å). 16,17,37−39 The spectroscopic response of single-molecule 40 and bulk liquid 30,33 water systems has been thoroughly investigated by means of density functional theory (DFT) approaches in the context of vibrational Stark spectroscopy, in which frequency shifts induced by intense EFs to selected vibrational modes are conveniently exploited as local probes. 41 An impressive recent study 42 has explored the accuracy of several DFT methods for simple (a)polar molecules placed under external intense EFs.…”
Section: ■ Introductionmentioning
confidence: 99%